Impacts of Influencers on Customer’s Purchase Intentions in Instagram - Mohammad Mersa Bayu Wibisono; Handi Prasetyanto; Borsak Sitanggang; Armedya Dewangga; Merry Maryati (Indonesian Business Review, 2023)
Social media in modern society has transformed into the main communication platform among people: those who are having interesting content will gain more followers and a bigger audience. Thus, the evolution of social networking has also evolved digitally with the rise of key opinion leaders or social media influencers. This new trend has created a new opportunity for influencers to monetize their exposure and followers into a new marketing method for brands to tap into and advertise their products to gain more awareness from influencers’ followers. This paper examines the impacts of influencers on customers’ purchase intentions on social media, especially on Instagram. The social identity construct is introduced in this paper as of influencers in marketing, which also looks at how followers' purchase intentions are influenced by the influencers' perceived expertise, opinion leadership, and interest-fit. Data from 308 respondents who use the Instagram platform were gathered through a digital poll of respondents in Indonesia (Jabodetabek). Trustworthiness and perceived expertise had a negligible impact on customers' purchasing intentions, according to the study. On the other hand, clients' purchase intentions were positively impacted by interest fit and opinion leadership. This paper will explain The theoretical and practical implications of these findings.